Memperkuat Nilai Kebangsaan Dengan Merawat Lingkungan (Lapangan Bola Voli) Di Desa Sukorejo - Muhammad Fajrul Falaah; Dimas Hanif Adi Baskoro; Bagus Setiawan (Institut Teknologi dan Bisnis Semarang, 2024)
This community service has been carried out in Sukorejo village, Wonosari District, Klaten Regency in order to strengthen love for the country and raise community awareness in caring for the village environment, especially public facilities. The problems currently faced are not yet maximally maintaining and beautifying the use of public facilities such as land for exercise as a means of establishing intense social relations as a form of strengthening national values. The method used in this activity is mutual cooperation to care for the environment in order to strengthen national values. The aim to be achieved in this community service is to provide a model of understanding and education to the surrounding community regarding the importance of caring for and beautifying the environment as an effort to foster shared responsibility for the blessings of gratitude that Almighty God has given to the Indonesian people, especially in the Sukorejo village environment.